Kepedulian Orang Tua Terhadap Pendidikan Agama Siswa - Dhin, Cut Nya (Jurnal Kinerja Kependidikan (JKK), 2020)
This study aims to determine the forms of concern, what factors influence the concern and differences in the achievement of religious education of students who are parents of Civil Servants and non Civil Servants at SMPN 9 Banda Aceh. This study is a quantitative field research by collecting data through observation, interview, questionnaire and documentation techniques. The results showed that there were already concerns of parents of Civil Servants and non Civil Servants towards the Islamic religious education of their children who were studying at SMPN 9 Banda Aceh. Concern is not because of status or profession, but because it is their responsibility as parents. The form of concern for parents (Civil Servants) and (non Civil Servants) is by ordering and controlling their children so that they are diligent in learning and practicing Islamic teachings well, taking their children to recitation centers and even teaching themselves at home. Concern of parents towards religious education both parents who are Civil Servants and non-Civil Servants are influenced by various factors, namely educational factors, environmental factors, busyness factors, lack of cooperation between teachers and parents of students. In addition, due to inadequate supporting facilities, even some students (7 students whose parents are Civil Servants and 3 students whose parents are non Civil Servants). Answering still less interest in the study of Islamic religious education at SMPS 9 Banda Aceh. Increased motivation and student achievement have no effect on the status of parents as Civil Servants or non Civil Servants. Learning achievement arises from oneself or others either because of the motivation of the teacher, parents, friends and so forth. All forms of motivation and achievement arises not because of parental employment status reasons